Bukti-bukti semiotika triadik charles pierce dalam puisi erlkonig - Ikhsani, Muhammad Iqbal; Albiruni, Fikri Fayyadh; Syahirah, Najla Esa (Fakultas Sastra, 2023)
This research will focus on a poetic analysis of the meaning in a poem Erlkönig by J.W. von Goethe using Charles Sanders Pierce's triadic analysis, namely: representamen, object, and interpretant. The qualitative method in the form of a literature review study was used in this research, using Sugiyono's research procedures of data description, reduction and selection. The study, which was conducted from April to May 2023, found that there are no research that shows triadic aspects of Goethe Erlkonig poem analysis yet. This research aims to appreciate and analyze literary works using Charles Sanders Pierce's triadic semiotic theory. The results obtained in the form of evidence of Pierce's triadic semiotic elements in the poem Erlkönig by Goethe. Representamen showed in a form of evidence that Goethe adapted Elveskud, and the next item is object, which showed in the result and discussion. Interpretant in this research showed in form of explanation in relation of Strum und Drang era in this writing of this poem. The result of this research fulfilled the focus to show the 3 triadic aspects of pierce theory. Kata Kunci: Erlkönig, Goethe, Semiotic, Pierce, Poem